Structural brain changes in early‐onset and late‐onset depression: An update of volumetric MRI findings. Issue 2 (June 2014) - Tittmann, Mandy; Günther, Thomas; Sacher, Julia; Himmerich, Hubertus; Villringer, Arno; Hegerl, Ulrich; Schönknecht, Peter
ABSTRACT Early‐onset (EOD) and late‐onset depression (LOD) are associated with different neuropsychological syndromes and structural brain changes. In this article, neuroimaging studies examining structural brain changes in elderly depressed patients are reviewed. The presented findings support current assumptions that depression in the elderly generally is associated with volume reductions in brain structures, notably in the hippocampus and the orbitofrontal cortex (OFC). Concerning structural cerebral differences between EOD and LOD, the review yielded conflicting results—only for OFC, but not for amygdala or hippocampus, pronounced effects in LOD than in EOD can be assumed. © 2014 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 24, 149–160, 2014